Plan de desarrollo turístico sostenible para el fortalecimiento de la actividad turística post terremoto en la región costa norte de Manabí. - Nevárez Vélez, Maleny Merillene (2018)
This ungoing investigation has a general objective to elaborate a plan for sostainable touristic development to strenghten the touristic activity in the costal región of the North Manabi after the earthquake of April 16 2016. They propose a non tranversal expermintal metodological design using an inductive and dectuve method. The implemented methodology exists out of four stages. In the first stage they realize a situacional touristic diagnostic to indentify existing problems of the earthquake after math regarding resources, atractions and touristic services. Every representative of the department of tourism is using polls and interviews. The second stage consists in indentifying strategies by using the SWOT matrix. This resulted in a main weakness of coordination between the departments of tourism, counties and local municipals with enterprising people. The third stage consists in the outwork of sostainable touristic development for the North of Manabi, where they determine the objectives, misión and cooperative goals. They implement nine programs and twenty projects to improve the activity in the touristic área. The fourth stage consists in the control and execution of the strategies of al the established programs and projects. They have to be strictly monitored for quality control, deadline and achiving the requires standards. The conlude that a stratigic plan to strenghten the touristic activity after the eartquake en the north part of the province of Manabi is trancendental and a founding base for a suitable reactivation of the región.